If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + -30 = 3y + -54 Reorder the terms: -30 + 2y = 3y + -54 Reorder the terms: -30 + 2y = -54 + 3y Solving -30 + 2y = -54 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. -30 + 2y + -3y = -54 + 3y + -3y Combine like terms: 2y + -3y = -1y -30 + -1y = -54 + 3y + -3y Combine like terms: 3y + -3y = 0 -30 + -1y = -54 + 0 -30 + -1y = -54 Add '30' to each side of the equation. -30 + 30 + -1y = -54 + 30 Combine like terms: -30 + 30 = 0 0 + -1y = -54 + 30 -1y = -54 + 30 Combine like terms: -54 + 30 = -24 -1y = -24 Divide each side by '-1'. y = 24 Simplifying y = 24
| (11x-25)+(24+10)=90 | | 3+10b-5-4b= | | 3y+8=y+66 | | -48=5c-2 | | 2x^2-13=11 | | 0.12x+1=0.880 | | 2y=y+50 | | -80=8(7-2x)-(2x-8) | | 11x-4=10x+25 | | 16y-8(3y-2)=-2424 | | 6x+3+87= | | 13y-17+145=180 | | 1.3y-18=2 | | -10+5x=-55 | | 2x=4x-50 | | 2s=s+22 | | 4h-6=7 | | 2t=t+100 | | 3x+7+56= | | 4b=b+33 | | 2y=y+38 | | 45=8(b-3)+5 | | 8(b+3)=3(2b-4) | | 3x+6+48= | | 8x^3+16x^2+20x+0=0 | | 6n+5=3-5n | | -4(w+6)-6w= | | 6x+x=x+3x+16 | | 4g+5+5g=9m-6 | | 6n+5=3+5n | | x/5-8=13 | | 3n-6=5n-10 |